Hipnoterapi Untuk Menurunkan Nyeri Dismenore : Tinjauan Pustaka - Adzkia, Maratul; Kartika, Imelda Rahmayunia (REAL in Nursing Journal, 2020)
This literature review was made aiming to increase knowledge and enrich our Evidence Based health workers about Hypnoteraphy Treatment for menstrual pain. By doing a number of stages in the making, namely looking for his journal on Google (Proques, Google Education, Pubmed) with the keywords "Desminore and Hypnotherapy for Pain" up to 20 journals which have been published in the last 10 years. Of the 20 selected journals taken 9 more journals discussed in depth which are displayed in the form of tables and their discussion. almost all experiments carried out showed results. The average woman who experienced desminore pain after hypnotherapy could reduce the level of pain.Keywords: Desminore, Hypnotherapy for Pain